Translating discourses of educational policy into the daily life of two Chilean municipal schools: Using the medical metaphor as a means for the analysis - Felipe Acuña; Universidad de Chile; Jenny Assaél; Universidad de Chile; Paulina Contreras; Universidad de Chile; Belén Peralta; Universidad de Chile (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2014)
This work seeks to contribute to the reflection and critical analysis of the current educational policy by analyzing the translation of the Chilean neo-liberal educational policy at the educational community level. We conducted our work through an ethnographic approach, using material produced in two ethnographies of municipal schools. We used the analysis of the metaphor “the school as a sick body” in order to articulate the analysis of the policy as texts and as a discourse. The main findings were: i) students are simultaneously desired since they entail additional resources and rejected since they are responsible for enrollment reduction and increased teaching hardship; ii) school communities recognize the need to receive external help, but they criticize the intervention. Finally, we conclude that discourses about school efficacy improvement and accountability are subordinate to the discourse on education as a market good.